Contracting arrangements and public private partnerships for sustainable development - Ehtisham Ahmad; Annalisa Vinella; Kezhou Xiao (Public Sector Economics, 2018)

(untitled)
This paper extends the discussion of the investment cycle in Ahmad (#ref2700#2017#/ref2700#) (G24 paper), in which the questions concerning “what” to invest in and “where” are addressed. This paper examines the “how” of investment for sustainable development, focusing on options for contracting arrangements, such as PPPs, that would help to involve the private sector, manage risks in the presence of asymmetric information, as well as uncertainty about climate change. It also addresses the strengthening of national and local institutions and the possible role of international financial institutions. In discussing the investment options, the paper also updates a G24 review of the empirical and theoretical literature on involving the private sector involvement in public investments (Ahmad et al., #ref2700#2018#/ref2700#).